Between-Match Variability of Peak Power Output and Creatine Kinase Responses to Soccer Match-Play. Issue 8 (August 2015) - Russell, Mark; Northeast, Jonny; Atkinson, Greg; Shearer, David A.; Sparkes, William; Cook, Christian J.; Kilduff, Liam P.
Abstract : Abstract: Russell, M, Northeast, J, Atkinson, G, Shearer, DA, Sparkes, W, Cook, CJ, and Kilduff, LP. Between-match variability of peak power output and creatine kinase responses to soccer match-play. J Strength Cond Res 29(8): 2079–2085, 2015—Postmatch assessments of peak power output (PPO) during countermovement jumps and creatine kinase (CK) concentrations are common markers of recovery status in soccer players. Yet, the impact of soccer match-play on recovery in the 48 hours after competition is unclear, and the between-match variability of these responses has not been examined. Fourteen reserve team players from an English Premier League club were examined over 1–4 matches per player. Creatine kinase and PPO were measured before, 24, and 48 hours after each match. Data were analyzed with within-subjects linear mixed models. Compared with the prematch baseline, PPO was 237 ± 170 W and 98 ± 168 W lower at 24 and 48 hours, respectively ( p ⩽ 0.005) and CK was elevated (24 hours: 334.8 ± 107.2 μ·L −1, 48 hours: 156.9 ± 121.0 μ·L −1 ; both p ⩽ 0.001) after match-play. These responses were consistent across the different matches and playing positions ( p > 0.05). Within-subject correlations between PPO and CK were significant ( r = −0.558; p ⩽ 0.005). The between-match variability of PPO was 10.9, 11.0, and 9.9%, respectively at baseline, 24 and 48 hours, whereas for CK, the variability was 41.7, 30.0, and 34.3%, respectively. These findings highlight that more than 48 hours are needed to restore metabolic and performance perturbations after soccer match-play, and that CK demonstrates greater between-match variability than PPO. Such information is likely to be of interest to those responsible for the design of training schedules in the days after a match and sports scientists whose responsibilities include the monitoring of recovery status in soccer players.